EKSPLORASI INOVASI DALAM PERENCANAAN PEMBELAJARAN MATEMATIKA DI MI MUHAMMADIYAH KARANGANYAR DALAM KONTEKS KEBIJAKAN MERDEKA BELAJAR - Nurjanah, Siti; Sutama; Achmad Fatoni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to explore innovations in mathematics lesson planning at MI Muhammadiyah Karanganyar within the context of the Merdeka Belajar policy. The research method used is qualitative with a case study approach, focused on fifth-grade teachers and students. Data were collected through observations, in-depth interviews, and document analysis. The research findings indicate that teachers have successfully implemented various innovations, such as diagnostic assessments and the use of engaging learning media, which can enhance students' motivation and learning outcomes. These innovations include the creation of creative Lesson Plans (RPP) and the formulation of teaching strategies that meet students' needs. Additionally, teachers utilize technology in the learning process to make the material more engaging and interactive. The implementation of diagnostic assessments helps in understanding students' strengths and weaknesses so that learning can be tailored to individual needs. The study also found that the implemented innovations can create a pleasant and conducive learning environment. This contributes to increased participation and enthusiasm of students in learning mathematics.